2023
DOI: 10.1111/jir.13093
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in people with and without intellectual disabilities: a systematic review and meta‐analysis

E. G. Browne,
J. R. King,
A. D. R. Surtees

Abstract: BackgroundSleep problems are regularly reported in people with intellectual disabilities. Recent years have seen a substantial increase in studies comparing sleep in people with intellectual disabilities to control participants, with an increase in the use of validated, objective measures. Emerging patterns of differences in sleep time and sleep quality warrant pooled investigation.MethodsA systematic search was conducted across three databases (Ovid Embase, PsycInfo and Medline) and returned all papers compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…At least a third of adults with ID will experience multiple sleep difficulties [30], with older adults, and those with a higher severity of ID and/or associated physical and mental health co-morbidities at higher risk [31].…”
Section: Other Sleep Disordersmentioning
confidence: 99%
“…At least a third of adults with ID will experience multiple sleep difficulties [30], with older adults, and those with a higher severity of ID and/or associated physical and mental health co-morbidities at higher risk [31].…”
Section: Other Sleep Disordersmentioning
confidence: 99%
“…The sleep-wake rhythm in older adults with intellectual disabilities (IDs) is often unstable and fragmented (Maaskant et al 2013). The instability and fragmentation are associated with sleep problems (Van De Wouw et al 2012;Van De Wouw et al 2013), which are found in up to 72% of this population (Van De Wouw et al 2012;Van De Wouw et al 2013) and are more common in people with IDs than in their typical developing peers (Surtees et al 2018;Böhmer et al 2020;Browne et al 2024). Sleep problems are associated with the high prevalence of depressive symptoms in older adults with IDs (Van De Wouw et al 2012;Hermans et al 2013;Maaskant et al 2013;Van De Wouw et al 2013).…”
Section: Introductionmentioning
confidence: 99%